Odpowiedzi

2010-01-10T20:48:55+01:00
X-3y=5
y+3x=-5

x=5+3y
y+3(5+3y)=-5
y+15+9y=-5
10y=-20
y=-2

x+6=5
x=5-6
x=-1

x=-1
y=-2
2 5 2
Najlepsza Odpowiedź!
2010-01-10T21:09:17+01:00
5=3x - y →y=3x-5
5x-2y=7

5x-2(3x-5) = 7
5x -6x +10 = 7
-x=7-10
-x=-3/:(-1)
x=3

y=3x-5
y=3*3 - 5
y=9 - 5
y=4
spr.5=3*3-4 → 9-4=5
5*3 -2*4=7
15 - 8 = 7



x-3y=5 /*(-3) → -3x+9y=-15
y+3x=-5
-3x+3x+9y+y=-15-5
10y= -20/:10
y=-2

-2+3x=-5
3x=-5+2
3x=-3/:3
x=-1
spr. -1-3*(-2) = 5
-1+6=5
-2+3*(-1)=-5
-2-3=-5



3x+y=5
2x-y=0

3x+2x+y-y=5+0
5x=5/:5
x=1

2*1 -y=0
2-y=o
-y=-2/:(-1)
y=2

spr.3*1 +2=5
2*1 -2 = 0


2x-y=5
x+y=4
2x+x-y+y=5+4
3x=9/:3
x=3

2*3 -y=5
6-y=5
-y=5-6
-y=-1/:(-1)
y=1

spr.2*3-1=5
6-1=5
3+1=4
4=4
2010-01-10T21:10:42+01:00
5=3x - y
5x-2y=7
3x-y=5 /*(-2)
5x-2y=7
-6x+2y=-10
5x-2y=7
-x =-3/*(-1)
x=3
5=3*3-y
5=9-y
5-9=-y
-4=-y/*(-1)
4=y


x-3y=5 /*(-3)
y+3x=-5
-3x +9y=-15
y+3x=-5
10y=-20/:10
y=-2
x-3*(-2)=5
x+6=5
x=5-6
x=-1

3x+y=5
2x-y=0
5x=5/:5
x=1
3x+y=5
3*1+y=5
3+y=5
y=5-3
y=2


2x-y=5
x+y=4
3x=9/:3
x=3

2x-y=5
2*3-y=5
6-y=5
-y=5-6
-y=-1/*(-1)
y=1



2 5 2